Emotional Intelligence with Self Esteem in Adolescents Who Have Experienced Child Abuse In Sorong City - Lewerissa, Erin Claudia; Sarajar, Dewita Karema (Universitas Wiralodra, 2024)
Adolescence is often considered a transition period marked by significant changes. It is seen as a period of transition, a challenging age, and a time of searching for identity. At the same time, adolescence is also considered the threshold of adulthood because it involves uncertainty and lack of control. Family dynamics also tend to change during the adolescent phase, including increased conflict between teenagers and parents, changes in roles and responsibilities, and changes in expectations placed on teenagers. A mismatch between parental expectations and adolescent behavior can increase the risk of conflict, which in turn can lead to incidents of child abuse. This research aims to determine the relationship between emotional intelligence and self-esteem in adolescents who have experienced child abuse in Sorong City. The method used is quantitative research with a correlational design. A total of 64 teenagers aged 12-21 years and residing in Malagusa sub-district, Sorong City were participants in this research who were taken using a saturated sampling technique. Research measurements used the Wong & Law Emotional Intelligence Scale (WLES) and The Rosenberg Self Esteem Scale (RSES). The research data analysis method uses Pearson Correlation. The research results show that there is a significant positive relationship between emotional intelligence and self-esteem of 0.949 with a significance of 0.000 (p<0.01). This shows that emotional intelligence plays a major and important role in relation to the level of self-esteem of teenagers who have experienced child abuse in Sorong City.